2014
DOI: 10.2478/s13545-014-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Predation of adult large diving beetles Dytiscus marginalis (Linnaeus, 1758), Dytiscus circumcinctus (Ahrens, 1811) and Cybister lateralimarginalis (De Geer, 1774) (Coleoptera: Dytiscidae) on fish fry

Abstract: The presented study describes the presence of fish fry in the diet of imagines of large Dytiscidae. The study was conducted between March and September in 2012 and 2013. A total of 163 large, aquatic, diving beetles were caught, which represented the following species: Dytiscus marginalis, Dytiscus circumcinctus, Cybister lateralimarginalis. Fish were identified by scales, bones, vertebrae, pharyngeal teeth. Insects were identified by epicrania, mandibles, hooks, limbs, body segments, eyes and wings. Crustacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…In freshwater environments, diving beetles (Coleoptera: Dytiscidae) are carnivorous during both the larval and adult stages; larvae are exclusively predatory, whereas adults also scavenge for food (Culler et al ). They are known to prey on zooplankton, insects, gastropods, fish, amphibians and reptiles (Drummond & Wolfe ; Ohba ,b; Cobbaert et al ; Rosa et al ; Frelik ; Hayashi & Ohba ). In addition, a previous report described finding larval horsehair worms in the gut of an adult diving beetle, Dytiscus marginalis , in a laboratory experiment, which was attributed to predation on larval Lepidoptera infested with larval horsehair worms (Blunck ).…”
Section: Percentage Of Prey Animals Captured By Larval Cybister Brevimentioning
confidence: 99%
“…In freshwater environments, diving beetles (Coleoptera: Dytiscidae) are carnivorous during both the larval and adult stages; larvae are exclusively predatory, whereas adults also scavenge for food (Culler et al ). They are known to prey on zooplankton, insects, gastropods, fish, amphibians and reptiles (Drummond & Wolfe ; Ohba ,b; Cobbaert et al ; Rosa et al ; Frelik ; Hayashi & Ohba ). In addition, a previous report described finding larval horsehair worms in the gut of an adult diving beetle, Dytiscus marginalis , in a laboratory experiment, which was attributed to predation on larval Lepidoptera infested with larval horsehair worms (Blunck ).…”
Section: Percentage Of Prey Animals Captured By Larval Cybister Brevimentioning
confidence: 99%
“…Scientists have been investigating the diet preference and prey compositions of dytiscids through food choice experiments, and many studies have found that adults scavenge for animal carcasses even with preference over live prey (Velasco & Millan, 1998; Kehl & Dettner, 2003; Bofill & Yee, 2019). Examinations of gut contents in wild‐caught dytiscid adults indicated high diversity of their food sources, including zooplankton, invertebrates, and vertebrates (Frelik, 2014; Frelik & Pakulnicka, 2015), which potentially implies a less selective scavenger lifestyle. Most studies on foraging strategies of dytiscids so far have been focused on predation at their larval stage (e.g., Michel & Adams, 2009; Yee, 2010), leaving scavenging tactics of adults unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Larvae swim out of their incubators after 3–4 weeks (depending on the water temperature) band form shoals of several to several hundred larvae very soon thereafter [ 13 , 14 ]. They prefer shallow places, with dense vegetation, where they are not exposed to attacks of predators, i.e., other fish and aquatic insects, larvae and adults, such as great diving beetle Dytiscus marginalis , the beetle Cybister lateralimarginalis [ 15 ], or dragonfly larvae Anax sp. of the family Aeshnidae [ 16 ].…”
Section: Introductionmentioning
confidence: 99%